Moving towards an "Eagle-Eyed" society: Malaysian perspective - Zulhuda, Sonny; Khan, Md. Zubair Kasem (Global Press, 2014)
With the profound sophistication of technologies throughout the globe, the nature of crimes has also been changed tremendously which redound to shifting from physical to virtual paradigm. Furthermore, this high-tech has also surplus the sphere of crimes to economic, social, political, even cultural arenas, mostly through the internet. In consequence, to cope up with such cyber threats, the efficacy of electronic surveillance has been intensifying ostentatiously over the last two decades, predominantly in the west. Malaysia too has introduced such modern technology of e-surveillance owing to ensure security in both national and transnational levels by the adoptions of Security Offences (Special Measures) Act (SOSMA) 2012 and the Prevention of Crime Act (PCA) 2014. However, such enactments have raised a new controversy by allowing police to impose electronic monitoring devices as well as other types of technologically-aided surveillance over the arrested or suspected crime offender’s body. All these maneuvers undoubtedly intersect the very basic notion of individuals’ data privacy and freedom of liberty which are shielded by the Federal Constitution of Malaysia to some extent. With latest legislative and judicial supports on the right to data privacy of the citizens of Malaysia, the question now emerge on whether this trend will be short-lived by the newly passed security laws such as the SOSMA 2012 and PCA 2014 which empower electronic surveillance to the law enforcement? The purpose of the author is to delineate the application of e-surveillance in Malaysia under these security related enactments and find the loopholes in implementing such legislation. Data from journals and books have taken into consideration to dissect these conceptions. It also have cogitated some prominent decisions of the judges throughout the world to enlighten this literature. This research is funded by the Fundamental Research Grant Scheme (FRGS) from the Ministry of Education, Malaysia.